2009
DOI: 10.3171/2009.3.spine08196
|View full text |Cite
|
Sign up to set email alerts
|

Simplified harvest of autologous pericranium for duraplasty in Chiari malformation Type I

Abstract: The authors describe a method of harvesting autologous pericranium for duraplasty in patients with Chiari malformation Type I (CM-I) that avoids excessive exposure or a second incision. Nonautologous dural grafts have been associated with numerous complications including hemorrhage, bacteria and virus transmission, fatal Creutzfeldt-Jakob disease transmission, foreign body reaction, systemic immune response, excessive scarring, slower healing, premature graft dissolution, and wound dehiscence. Autogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…A fourth study[25] comparing pericranium versus synthetic graft was identified. [14] However, it dealt with brain tumor resection in addition to Chiari decompression and was therefore excluded. A fifth study comparing autologous and nonautologous graft material was excluded because the full text was only available in Chinese (abstract in English).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A fourth study[25] comparing pericranium versus synthetic graft was identified. [14] However, it dealt with brain tumor resection in addition to Chiari decompression and was therefore excluded. A fifth study comparing autologous and nonautologous graft material was excluded because the full text was only available in Chinese (abstract in English).…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantages of nonautologous dural grafts include an increased risk of hemorrhage, often with silastic grafts,[142427] bacterial and viral transmission; Creutzfeldt-Jakob disease transmission, exclusively with cadaveric graft;[142736] eosinophilic-aseptic meningitis;[37] foreign body reaction and scarring;[14] increased wound healing time;[14] premature graft dissolution;[14] and wound dehiscence. [14] In the case of xenogenic pericardium, specifically bovine pericardium, the potential for bovine spongiform encephalopathy exists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have examined a variety of dural substitutes for use when primary dural closure is not possible [1][2][3]. Many techniques have been suggested, including use of a composite polyglactin 910 / poly-pdioxanone mesh patch [4], monolayer and bilayer collagen matrices [5][6][7][8][9], polytetrafluoroethylene [10][11][12][13], crescent durotomies for midline suboccipital craniotomies [14], and autologous pericranium [1,15]. Of these various dural substitutes, autologous pericranium is favorable due to lack of immunogenic response, low risk of infection, flexibility, and ease of use.…”
Section: Introductionmentioning
confidence: 99%